Multimarket linkages, buyer power, and the productivity puzzle - Noriaki Matsushima; Laixun Zhao (Osaka University, Institute of Social and Economic Research (ISER), 2010)
This paper examines the relationship between firms' productivity improvement and the volume of exports, and shows that it can be sometimes negative. Specifically, we simultaneously take into account intermediate retailers (i.e., vertically) and multimarket linkages (i.e., horizontally). We find that an improvement of the manufacturing productivity affects the bargained wholesale prices in opposite directions in asymmetric markets, causing retailers to make corresponding changes that look surprising. This result can explain for the empirical productivity puzzle found in Ghemawat et al. (2010). Related to this issue is the relationship between buyer power (caused by a retail merger) and profitability. Contrary to the existing literature, in an extended setup, we find that the merger between the downstream duopolists does not improve their profits if their bargaining power is strong vs. upstream suppliers.
Keywords: L12; L14; F12; F23; 330; Vertical Structure; Market power; Productivity; Multi-Market Bargaining; Internationaler Wettbewerb; Interregionaler Handel; Marktmacht; Produktivität; Zwei-Länder-Modell; Theorie